Math, asked by Anonymous, 1 year ago

Find x
 \frac{ {6}^{x} }{ {6}^{ - 2} }  =  {6}^{3}

Answers

Answered by Martin84
0

Answer:

1

Step-by-step explanation:

 \frac{ {6}^{ x} }{ {6}^{ - 2} }  =  {6}^{3}  \\  {6}^{x}  =  {6}^{ - 2}  \times  {6}^{3}  \\  {6}^{x}  =  {6}^{1}  \\ x = 1

Answered by Thatsomeone
0

Answer:

X = 1

Step-by-step explanation:

 \frac{ {6}^{x} }{ {6}^{ - 2} }  =  {6}^{3}  \\  \\  \\  {6}^{x + 2}  =  {6}^{3}  \\  \\  \\ x + 2 = 3 \\  \\  \\ x = 1

THANKS!!

Similar questions